A study of the fundamental and adult education movement in the Philippines - De Bunye, Sofia R. 1921- (Quezon City, Philippines College of Education, University of the Philippines Diliman, 1953)
The major problem of this investigation is to determine the various factors affecting the fundamental and adult education in the Philippines.
Thesis (M.A.)--University of the Philippines, Diliman.
Keywords: Education of adults